2020
DOI: 10.1177/1941738120955184
|View full text |Cite
|
Sign up to set email alerts
|

Functional Resistance Training to Improve Knee Strength and Function After Acute Anterior Cruciate Ligament Reconstruction: A Case Study

Abstract: Background: Thigh muscle weakness after anterior cruciate ligament reconstruction (ACLR) can persist after returning to activity. While resistance training can improve muscle function, “nonfunctional” training methods are not optimal for inducing transfer of benefits to activities such as walking. Here, we tested the feasibility of a novel functional resistance training (FRT) approach to restore strength and function in an individual with ACLR. Hypothesis: FRT would improve knee strength and function after ACL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 72 publications
2
4
0
Order By: Relevance
“…Two modalities of resistance training, which differed in terms of surface condition and intensity, were considered in the present study. The 1RM strength parameters of the upper and lower limb and muscle mass observed in our study are consistent with those indicated in similar studies (Soligon et al, 2020;Brown et al, 2021;Hamid et al, 2022). Kibele and Behm (Maté-Muñoz et al, 2014) reported that the traditional resistance training characteristics were to perform higher overload weights than in functional resistance training, which could also obtain similar muscle strength responses with the use of lower resistive load under unstable condition.…”
Section: Discussionsupporting
confidence: 93%
“…Two modalities of resistance training, which differed in terms of surface condition and intensity, were considered in the present study. The 1RM strength parameters of the upper and lower limb and muscle mass observed in our study are consistent with those indicated in similar studies (Soligon et al, 2020;Brown et al, 2021;Hamid et al, 2022). Kibele and Behm (Maté-Muñoz et al, 2014) reported that the traditional resistance training characteristics were to perform higher overload weights than in functional resistance training, which could also obtain similar muscle strength responses with the use of lower resistive load under unstable condition.…”
Section: Discussionsupporting
confidence: 93%
“…Two modalities of resistance training, which differed in terms of surface condition and intensity, were considered in the present study. The 1RM strength parameters of the upper and lower limb and muscle mass observed in our study are consistent with those indicated in similar studies [29][30][31]. Kibele and Behm [19] reported that the traditional resistance training characteristics were to perform higher overload weights than in functional resistance training, which could also obtain similar muscle strength responses with the use of lower resistive load under unstable condition.…”
Section: Quantifying Internal Training Loadsupporting
confidence: 92%
“…A lower training load was better than a higher load when similar training volume was performed (R-CAVI decrease: 7.4% vs. 8.2%; L-CAVI decrease: 6.2% vs. 9.4%). [45][46][47][48][49]. Kibele and Behm reported that the TRT characteristics were to perform higher overload weights than in FRT with unstable conditions [50], and to produce similar muscle strength responses by changing surface conditions [49].…”
Section: Discussionmentioning
confidence: 99%